Deixis in Conan Gray’s “Wish You Were Sober” and “Checkmate” Song Lyrics - Gitayani, Ni Nyoman Tri; Sutjiati Beratha, Ni Luh; Isnu Maharani, Sang Ayu (Humanis, 2023)
In conducting communication, deixis becomes a significant concern for people in improving their understanding of utterance usage. By learning deixis well, listeners can avoid misinterpretation in understanding the context of utterances, one of them while listening to the songs. Based on this phenomenon, this article aimed at identifying the types of deixis and analyzing the reference meaning of deixis used in Conan Gray’s “Wish You Were Sober” and “Checkmate” song lyrics. This article dealt with the qualitative method, while the documentation method was applied in collecting the data. The collected data were analyzed based on the deixis theory proposed by Cruse and the context of the situation developed by Holmes. The results showed the use of all types of deixis, namely the person, spatial, temporal, social, and discourse deixis. These types of deixis had reference meanings in pointing to participants involved in the songs, the location of participants, the time reference, the social relationship among the participants, and the prior or future discourse elements found in Conan Gray’s song lyrics.